PENGUNGKAPAN EMISI KARBON UNTUK MENINGKATKAN NILAI PERUSAHAAN: APAKAH KINERJA KEUANGAN MAMPU MEMODERASI? - Fitriana, Aning; Maharani, Destin Alfianika; Amelia, Shela Rizqi; Pangestika, Lia Widya (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2024)
Company value is an important indicator that provides signals regarding principal prosperity. This research investigates the impact of carbon emission disclosure on company value, with financial performance as a moderator. The research sample was 84 SRI-KEHATI-indexed companies for the 2019-2022 period, which were analyzed using multiple linear regression with Moderated Regression Analysis (MRA). The study's results partially showed a significant positive effect of carbon emission disclosure on company value. As measured by ROA, financial performance could not moderate the effect of carbon emission disclosure on company value. This finding indicates that financial performance does not guarantee that the company has sufficient funds to disclose carbon emission costs. This study supports Signaling Theory regarding the important role of information disclosure in increasing company value.